Catalisadores de Pt suportados, obtidos pelo método solgel : efeito do cério na atividade e estabilidade nas reações de reforma do metano - Ferreira, Adriana Paula (2009)
The effect of Ce as a structural and electronic promoter on the activity and stability of Pt catalysts supported on Al2O3 for methane reforming reactions were investigated to elucidate the metal-support interaction. Pt/Al2O3 and Pt/CeO2-Al2O3 catalysts were prepared by conventional method of wet impregnation on commercial supports and on CeO2- Al2O3 mixed oxides obtained by sol-gel method, which were studied to emphasize the alumina properties promoted by CeO2 as a more homogeneous and stable system. The metalsupport interface of Pt catalysts was also explored by the one-step sol-gel preparation method. The samples were characterized by chemical analysis, N2 physissorption, thermogravimetry, X-ray diffraction (XRD), 27Al nuclear magnetic resonance (RMN), scattering (SEM) and transmission electronic microscopy (TEM), cycloexane dehydrogenation (metal dispersion), temperature programmed reduction (TPR-H2), infrared diffuse reflectance spectroscopy with Fourier transform of the CO adsorption (DRIFTS-CO), X-ray photoelectronic spectroscopy (XPS) and in situ X-ray absorption spectroscopy (XAS). The Pt/CeO2-Al2O3 catalysts exhibit higher activities and stabilities than Pt/Al2O3, which are even better when Pt is supported on CeO2-Al2O3 mixed oxide obtained by sol-gel method. Physical-chemistry properties and the stability of the mixed oxides depend on Ce content, temperature and atmosphere of thermal treatment. TEM data show deactivation of Pt/Al2O3 catalysts is due to strong Pt agglomeration. Ce presence makes the support more stable and anchors Pt in a better way. In situ XAS analysis reveal Pt is reduced by the heating under partial oxidation of methane (POM), when the catalysts ignition occurs. Ce presence reduces this temperature and promotes Pt reoxidation after the cooling under POM conditions, indicating the electronic transfer between Pt and Ce that is also confirmed by Pt and Ce oxidation states changes during POM and oxy-reduction cycles. In situ EXAFS results show the Pt-O-Ce interaction and reveal Pt clusters present morphological changes with temperature increasing. The oxidation of deposited carbon on metal surface via metal-support interface (evidenced by sol-gel method preparation) confers higher activity to the Pt/CeO2- Al2O3 catalysts and shows CH4 reforming reactions are controlled by two limiting steps strongly dependents on the temperature: methane dissociation and carbon oxidation. Massa spectrometry data during the POM show this reaction occurs by indirect mechanism (combustion-reforming).